How should milk be priced in the future? - Bob Cropp (Kansas Agricultural Experiment Station Research Reports, 1996)
Milk pricing will continue to change. Clearly, the dairy industry will continue the trend toward MCP. The federal dairy price support program will terminate at the end of 1999. Changes will occur in federal order pricing. The FAIR ACT of 1996 requires some changes. Pricing provisions must be market oriented. The U.S. dairy industry must be competitive internationally. Federal order provisions must provide less rather than more regulation. Federal order prices must be minimum prices allowing for industry pricing above those prices. Markets are national. Hence, California should be a part of the same pricing system. Compacts such as the Northeast Interstate Compact should not be allowed.; Dairy Day, 1996, Kansas State University, Manhattan, KS, 1996;
Keywords: Dairy Day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-115-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 771; Milk marketing; Milk price